(untitled) (Journal of Medical & Health Sciences Review, 2025)
Nitrogen dope Carbon Dots (NCDs) were prepared from precursor compound having promising potential for the selective up take of Pd nano crystals. A calculated amount of the dried carbon dots dispersed in distilled water was subjected to spectrofluorimetric analysis which showed significant fluorescence. Carbon dots revealed maximum emission at 450nm followed by excitation at 370 nm. Well architect carbon dots showed selective up take for Pd octahedral as compared to Pd cubic nano crystals. The uptake of Pd octahedron nano crystals was maximum at carbon dots (10 hrs autoclaved) which showed 89.7% as compared to 5 hrs and 15 hrs which were 84.4% and 31.7% respectively. While the maximum uptake of Pd cubic nanocrystals on 5hrs, 10hrs and 15 hrs autoclaved carbon dots was found respectively to be negligible, 21.72% and 15.59%. Furthermore, Pd-NCDs finds applicability for catalyzing can be used in Heck reactions.